(untitled) (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This study aims to explore the type of Teacher Talk used by Indonesian pre-service teachers in teaching Indonesian as a foreign language (BIPA) in Australian classrooms. Here, the teachers used English to set a common language in the classroom. Open-ended questionnaires and interviews were conducted to find out the type of Teacher Talk and gain teachers’ perspectives during the teaching process from four participants. The data collected revealed six types of Teacher Talk they used in the classroom and were categorized using Flanders Interaction Analysis Categories (FIAC). It shows that using English in the classroom could develop comprehension interactions. Thus, it enhances students’ willingness and confidence to interact and engage during the learning process. Moreover, using English to explain Indonesian helps students to understand the materials. Therefore, this study challenges existing hypotheses in teaching foreign languages and shows that using students’ first language also could help students in learning a new language. Even so, providing activities related to the target language is still important.